Emulsion‐Templated Macroporous Carbons Synthesized By Hydrothermal Carbonization and their Application for the Enzymatic Oxidation of Glucose. Issue 4 (11th March 2013) - Brun, Nicolas; Edembe, Lise; Gounel, Sébastien; Mano, Nicolas; Titirici, Magdalena M.
Abstract Carbon‐based monoliths have been designed using a simple synthetic pathway based on using high internal phase emulsion (HIPE) as a soft template to confine the polymerization and hydrothermal carbonization of saccharide derivatives (furfural) and phenolic compounds (phloroglucinol). Monosaccharides can be isolated from the cellulosic fraction of lignocellulosic biomass and phloroglucinol can be extracted from the bark of fruit trees; however, this approach constitutes an interesting sustainable synthetic route. The macroscopic characteristics can be easily modulated; a high macroporosity and total pore volume of up to 98 % and 18 cm3 g−1 have been obtained, respectively. After further thermal treatment under inert atmosphere, the as‐synthesized macroporous carbonized HIPEs (carbo‐HIPEs) have shaping capabilities relating to interesting mechanical properties as well as a high electrical conductivity of up to 300 S m−1. These conductive foams exhibit a hierarchical structure associated with the presence of both meso‐ and micropores that exhibit specific Brunauer–Emmett–Teller (BET) surface areas and DFT total pore volumes up to 730 m2 g−1 and 0.313 cm3 g−1, respectively. Because of their attractive structural characteristics and intrinsic properties, these macroporous monoliths have been incorporated as a proof of principle within electrochemical devices as modified thin carbon disc electrodes. A promising two‐fold improvement in the catalytic current is observed for the electrooxidation of glucose after the immobilization of a glucose oxidase‐based biocatalytic mixture onto the carbo‐HIPE electrodes compared to that observed if using commercial glassy carbon electrodes.